PERSEPSI DAN MOTIVASI WISATAWAN NUSANTARA KE GUNUNG BROMO PADA MASA PANDEMI - Zainul Mustofa; Ni Made Oka Karini; LGLK. Dewi (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
Tourists flock to travel to relieve boredom after the government quarantine or known as revenge tourism. Mount Bromo is a tourist attraction that attracts domestic tourists. Knowing the motivation of tourists will help in tourism marketing planning and benchmarks for the quality of a tourist attraction can be known based on tourist perceptions. To determine the perceptions and motivations of domestic tourists in this study used descriptive quantitative and qualitative descriptive research methods. Data collection techniques using questionnaires, observation, interviews, documentation and literature study. In determining the respondents, the researchers used accidental sampling. The results obtained state that the perception of domestic tourists visiting Mount Bromo on the 4A component (attraction, ancillary, accesibility & amenity) is overall good, with the attraction component getting the highest score and the accessibility component getting the lowest score. The motivation for tourists to visit Mount Bromo during the pandemic is dominated by the desire to escape from routine indicator, which means that tourists travel on tourist trips to get out of the tedious daily routine after being quarantined due to COVID-19. Meanwhile, the motivation that attracts domestic tourists visiting Mount Bromo is the Marketed image of the destination or Mount Bromo which is widely known by the public for its beauty.